Professoras da educação infantil de Belém do Pará: histórias de leitoras - GOMES, Elaine Ribeiro (Universidade Federal do Pará, 2011)
The present work is tied with the research line resume and formation of professors and intended to investigate the practical ones of reading of the teachers of the infantile education of the Municipal Public of the City of Belém. The argument on the reading was based, mainly, in: Kleiman, Silva, Lerner, Barbosa, Zilberman, Freire and Lajolo that understand the reading as an activity of construction of directions, in a dynamic relation between text and reader, one practical partner-interaction, partner-cultural or partner-historical. In the scope of the practical ones of reading, it served of reference Roger Chartier that approaches the practical ones of reading as a process of construction, developed for authentic readers in concrete situations, through processes diversified in relation to the act to read. This is a amount-qualitative research, of descriptive and interpretative matrix, that it used as instruments for the production of the data the questionnaire and the narratives of the teachers. The narratives had been chosen as way inquiry theoretician-method, on the basis of authors as Walter Benjamin, Larrosa, Thompson, Bossi, Delgado, among others. The social environment of this inquiry had been four Units of Infantile Education of the City of Belém, that take care of to children of 6 months the 5 years of age in full time and part-time. It counted on the participation of twenty and seven teachers, in the first phase and with nineteen teachers, in the second phase. The analysis was structuralized in accordance with the context of the practical ones of reading, the familiar one, the pertaining to school, the professional and the current context. The main results point that: 59% of the teachers had its first contact with the reading in house; 44% made responsible the parents for this insertion; 37% affirmed that its experience of reading in the school was good; 14% confirmed that the didactic book is the read and used support more; 16% of the teachers reads with the intention to prepare lessons; 74% of the teachers had affirmed that they like to read; 40% carried through this practical frequent; 40% of the teachers if had called as good readers; 44.4% dedicated less than two hours per day to the reading and 81.5% carried through this practical in house. Therefore, the teachers keep a relation with the reading differentiated and singular, being used to take care of its personal and professional necessities. The practical ones of reading of the teachers if constitute in different situations, in diverse contexts and ways to read.